Hubungan antara Penggunaan Chatgpt dengan Digital Skills Mahasiswa PPKN Universitas Pendidikan Indonesia - Windi Nursyahfitri; Leni Anggraeni; Pitria Sopianingsih (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the relationship between the use of ChatGPT and the digital skills of students in the Civic Education Study Program at the Indonesia University of Education. The background of this research is based on the rapid advancement of technology, particularly artificial intelligence such as ChatGPT, which has transformed the way students access information, complete assignments, and engage in independent learning. This research employed a quantitative approach with a correlational method. Data were collected through questionnaires distributed to students and analyzed using Pearson correlation techniques. The results indicate a positive and significant relationship between the use of ChatGPT and students' digital skills. ChatGPT has been proven to assist students in enhancing critical thinking, communication, information management, and various technical abilities. These findings suggest that appropriate use of ChatGPT can support the development of digital competencies among students. The study provides implications for educational institutions in formulating policies on the ethical and educational use of technology.